Polymorphisms associated with type 1 diabetes mellitus - Rachman Indra Jaya; Yenni Riska Zettyana; Achirul Bakri; Yuwono Yuwono; Aditiawati Aditiawati (Indonesian Pediatric Society, 2018)
Background Type 1 diabetes mellitus (T1DM) is an organ-specific autoimmune disease characterized by T cell-mediated destruction of pancreatic islets. The genetic factors involved consist of at least five vulnerability genes: HLA, INS, CTLA-4, PTPN22, and IL2RA/CD25. Objective To investigate for associations of PTPN22-1123 G>C SNP and CTLA-4 +49A/G polymorphisms with T1DM. Methods Case and control groups underwent CTLA-4 +49A/G gene examination from June to December 2017, using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis. Results The study population consisted of 30 T1DM patients and 30 healthy subjects with no family history of diabetes or autoimmune diseases. With regards to the PTPN22-1123 G>C SNP, significantly more subjects with T1DM had the GC genotype than the GG genotype (OR 7.64; 95%CI 1.48 to 39.29; P=0.007). For the CTLA-4 +49A/G polymorphism, although the total number of G alleles in the case group was more than that of the control group (OR 2.286; 95%CI 0.804 to 6.945; P=0.118), there were no significant relationships between the frequency of G alleles (P=0.248) and genotypes GG or AG (P=0.293) with the incidence of T1DM. However, the PTPN22-1123 G>C SNP had a significantly positive association with T1DM, and may be considered as a risk factor for T1DM. In contrast, the CTLA-4 +49A/G polymorphism was not recognized as a risk susceptibility factor for T1DM. Conclusion These study confirms an association between PTPN22-1123 G>C SNP and T1DM, but no significant association between CTLA-4 +49A/G polymorphism and T1DM.